The weldability of experimental duplex stainless steels - Bulbulia, Zaid (My University, 1995)
Some authors define weldebility as the ability of a material to maintain its integrity, that is, its microstructure, corrosion and mechanical properties after welding. If such a stringent criteria is used to adequately describe the weldability of a material, then there would be but a few alloys which could be deemed weldable. As such this definition was found to be much to restrictive, and the author, has defined the term 'weldability' as the ability of a material to retain its corrosion and mechanical properties, such that the integrity of an as-welded structure under a particular service environment would be maintained to within acceptable limits. With this definition in mind the weldability of experimental low-nickel duplex stainless steels containing chromium, manganese and nitrogen were assessed. This assessment was based on the corrosion and mechanical properties of these alloys which were manual metal arc welded and plasma arc welded using a range of heat inputs. The results of these tests showed that the wrought and spun cast alloys are readily weldablility for the range of heat inputs considered. As a comparison to the welding charactristics of the high nitrogen alloys, a commercially available high carbon containing spun cast duplex stainless steel, MP36, alloy was used as a reference material. This alloy proved invaluable in that, not only was it possible to show that this alloy faked poorly in comparison with the high nitrogen containing alloys, but the effect of nitrogen as an interstitial element in welded stainless steels could be compared with that of carbon. The results of the latter evaluations showed that nitrogen, unlike carbon, does not have a detrimental effect on the corrosion or mechanical properties of these alloys, provided it is kept below the solubility limit of 'the stainless steel. The appearance of the microstructures of the high nitrogen containing alloys and the reference alloy in the solution annealed condition, were maintained after welding, with no rampant ferrite phase growth or extensive precipitation in the heat affected zone for the range of {Abbreviated Abstract. Open document to view full version}
A dissertation submitted to the University of the Witwatersrand in fulfillment of the degree of Master of Science, Engineering. Johannesburg, 1995.
Keywords: Stainless steel--Weldability